1995
DOI: 10.1007/bf00168030
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and three-dimensional imaging of epimyoepithelial islands in benign lymphoepithelial lesions

Abstract: Benign lymphoepithelial lesions of the salivary glands associated with Sjögren's syndrome are characterized by extensive infiltration of lymphoid cells, atrophy of acini and the presence of so-called epimyoepithelial islands. This report describes ultrastructural and three-dimensional reconstructive studies of epimyoepithelial islands performed at Tokyo Women's Medical College. Ultrastructural examination showed that these islands are composed mainly of epithelial cells containing intermediate filaments and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 11 publications
3
11
0
3
Order By: Relevance
“…These cells were sometimes in the process of forming vessel walls but at other times were not yet assembled into blood vessels. Although the duct epithelial nature of their constituent cells has been well investigated by ultrastructural [2,5,9,11,19,28,32,35,40,41] and immunohistochemical [3,15,16,21,22,26,27,32,38] studies, there has been no postulation of endothelial cell participation in the formation of LELs. Only Qin et al [29] reported von Willebrand factor-immunopositive capillaries in the inflammatory stroma, suggesting that an efficient blood supply elucidates regeneration and proliferation of epithelial cells in the formation of the LELs in a general sense.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cells were sometimes in the process of forming vessel walls but at other times were not yet assembled into blood vessels. Although the duct epithelial nature of their constituent cells has been well investigated by ultrastructural [2,5,9,11,19,28,32,35,40,41] and immunohistochemical [3,15,16,21,22,26,27,32,38] studies, there has been no postulation of endothelial cell participation in the formation of LELs. Only Qin et al [29] reported von Willebrand factor-immunopositive capillaries in the inflammatory stroma, suggesting that an efficient blood supply elucidates regeneration and proliferation of epithelial cells in the formation of the LELs in a general sense.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoepithelial sialadenitis (LESA [13], also referred to as benign lymphoepithelial lesion [2,9,40,41], lymphoepithelial lesion [3,5,18,27,30], myoepithelial sialadenitis (MESA) [10,11], Sögren-type sialadenitis [15], or autoimmune sialadenitis [21,22,32]) of the salivary glands is histologically characterized by an extensive infiltration of chronic inflammatory cells replacing the salivary parenchymal space, which is composed of acinar and ductal cells. In their full-grown stages, ductal cell remnants regenerate to form epimyoepithelial islands (EMIs), which sometimes show minimal ductal lumina but ultimately show solid epithelial nests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benign lymphoepithelial lesion (BLEL) [1], also referred to as lymphoepithelial sialadenitis (LESA), lymphoepithelial lesion [2], myoepithelial sialadenitis (MESA), Sjogren's-type sialadenitis [3], or autoimmune sialadenitis of the salivary glands, is characterized histologically by an extensive infiltration of chronic inflammatory cells that replace the salivary parenchymal space, which is composed of acinar and ductal cells [4]. Godwin [5] described BLEL as lymphoepithelial changes in major salivary glands associated with unilateral or bilateral gland enlargement in the absence of the clinical signs of SS (dry eyes and mouth).…”
Section: Introductionmentioning
confidence: 99%
“…Based on conventional and ultrastructural histology some groups supported this concept of a primary myoepithelial lesion, adding the more comprehensive term myoepithelial sialadenitis [5,10,12,33,34]. However, in a series of consecutive ultrastructural and immunohistochemical investigations the role of myoepithelial cells could not be substantiated [2,20,21,28,32,38].…”
Section: Introductionmentioning
confidence: 99%